Fabrication of magnetic tunnel junctions connected through a continuous free layer to enable spin logic devices. (6th February 2018) - Wan, Danny; Manfrini, Mauricio; Vaysset, Adrien; Souriau, Laurent; Wouters, Lennaert; Thiam, Arame; Raymenants, Eline; Sayan, Safak; Jussot, Julien; Swerts, Johan; Couet, Sebastien; Rassoul, Nouredine; et al.
Abstract: Magnetic tunnel junctions (MTJs) interconnected via a continuous ferromagnetic free layer were fabricated for spin torque majority gate (STMG) logic. The MTJs are biased independently and show magnetoelectric response under spin transfer torque. The electrical control of these devices paves the way to future spin logic devices based on domain wall (DW) motion. In particular, it is a significant step towards the realization of a majority gate. To our knowledge, this is the first fabrication of a cross-shaped free layer shared by several perpendicular MTJs. The fabrication process can be generalized to any geometry and any number of MTJs. Thus, this framework can be applied to other spin logic concepts based on magnetic interconnect. Moreover, it allows exploration of spin dynamics for logic applications.